1996
DOI: 10.1007/bf02399946
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific mitochondrial DNA variation in the Colorado potato beetle,Leptinotarsa decemlineata (Coleoptera: Chrysomelidae)

Abstract: Restriction endonuclease analyses of mitochondrial DNA (mtDNA) were used to examine genetic variability and population structure in Leptinotarsa decemlineata (Say). A group of three enzymes, EcoRI, HpaI, and PstI, was used to reveal polymorphism both within and among some of the 10 populations tested, yielding 16 haplotypes in combination. The frequencies of these 16 haplotypes differed significantly across geographic regions, indicating some partitioning of mtDNA haplotypes. Estimates of mtDNA sequence diverg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Restriction endonuclease digestion of mitochondrial DNA revealed the presence of 16 haplotypes of this beetle occurring in the USA (Azeredo-Espin et al 1996). An earlier study done using the same approach on 16 populations from the USA and one from Mexico showed five distinct mtDNA genotypes among the U.S. populations and high divergence between these genotypes and the genotype of the Mexican population.…”
Section: Resultsmentioning
confidence: 99%
“…Restriction endonuclease digestion of mitochondrial DNA revealed the presence of 16 haplotypes of this beetle occurring in the USA (Azeredo-Espin et al 1996). An earlier study done using the same approach on 16 populations from the USA and one from Mexico showed five distinct mtDNA genotypes among the U.S. populations and high divergence between these genotypes and the genotype of the Mexican population.…”
Section: Resultsmentioning
confidence: 99%
“…As a final possibility, there is some evidence that potato beetles in Washington appear to be less genetically diverse than beetles occurring elsewhere . Indeed, this unique, low‐diversity genetic make‐up may make a key contribution to the lack of insecticide resistance in Washington potato beetles.…”
Section: Getting Off the Treadmillmentioning
confidence: 86%
“…102 -104 Indeed, this unique, low-diversity genetic make-up may make a key contribution to the lack of insecticide resistance in Washington potato beetles. For example, Azeredo-Espin et al, 104 using restriction endonuclease analysis of mitochondrial DNA, found that potato beetles in Washington all fell into a single haplotype that was not found in any of the other nine geographically diverse populations that they examined (see the similar finding by Zehnder et al 102 ). Similarly, a widely dispersed haplotype found in each of the other nine populations was not found in Washington.…”
Section: Washington State -A Place Where Old Chemistries Still Workmentioning
confidence: 87%
See 1 more Smart Citation
“…To develop appropriate and effective integrated control strategies, CPB spatial distribution and migration must be well understood (Boiteau et al, 2003). Mitochondrial and nuclear DNA, had provided valuable information on colonization origins, the extent of genetic differentiation, and gene flow during the expansion of CPB in North America and Europe (Zehnder et al, 1992;Azeredo-Espin et al, 1996;Sidorenko & Berezovska, 2002;Grapputo et al, 2005).…”
Section: Introductionmentioning
confidence: 99%